Darcy-Forchheimer flow of maxwell nanofluid flow over a porous stretching sheet with Arrhenius activation energy and nield boundary conditions. (April 2023) - Jawad, Muhammad; Hameed, Maria Kirn; Nisar, Kottakkaran Sooppy; Majeed, Afraz Hussain
Abstract: This work investigates the effect of heat transfer and mass transfer on the convective Darcy-Forchheimer flow of a Maxwell nanofluid through a linear porous stretched sheet. In addition, the impacts of chemical reaction, thermal conductivity, and thermophoresis are investigated. The analysis of heat and mass transfer in the presence of nanoparticles in a Maxwell fluid under convective and nield conditions is examined. To convert the governing PDEs of velocity, temperature and nano concentration with activation energy into a couple of nonlinear ODEs we apply the appropriate similarity variables. Shooting method is applied to solve the set of highly nonlinear ordinarily differential equations numerically and obtained numerical results are associated with those gained by the help of MATLAB bvp4c solver and Mathematica ND-solve built in command. The influence of prominent parameters of interest like chemical effusion, Prandtl number, Biot number, radiative heat flux Brownian motion, Lewis number, thermophoresis parameter, magnetic parameter, Reynolds number, thermophoresis parameter, on, non-dimension velocity, heat and nano concentration distribution has been deliberated and heat transfer features is also encompassed. The numerical values obtained for defined profiles are presented through graphs and tables.